Okres budżetowy w ujęciu poznańskiej szkoły skarbowości - Małecki, Jerzy (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2012)
Poznań School of Public Finance was created in 1919 by professor Edward Taylor, a member of the Law and Economy Faculty of the Poznan´ University, and a mentor and moral role model for thousands of Polish lawyers and economists that followed. For political reasons, for fifty years after World War II, the research work of the Department of Financial Law of the University’s Law and Economy Faculty concentrated on budget laws. In that period Poznan´ became a leading research centre specialising in state and local finance in Poland. The paper presents selected dissertations of the researchers from the Department of Financial Law, devoted to the pioneering aspects of the budget period and long-term financial planning.